2022
DOI: 10.3390/vetsci9100526
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Diagnostic Techniques and Biomarkers of Canine Mammary Tumors

Abstract: Canine mammary tumors (CMTs) are considered a serious clinical problem in older bitches. Due to the high malignancy rate and poor prognosis, an early diagnosis is essential. This article is a summary of novel diagnostic techniques as well as the main biomarkers of CMTs. So far, CMTs are detected only when changes in mammary glands are clinically visible and surgical removal of the mass is the only recommended treatment. Proper diagnostics of CMT is especially important as they represent a very diverse group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…Molecular aspects of tumours (metabolism, gene expression, miRNAs and transcriptome sequencing markers) are crucial for a proper understanding of tumour genesis and the application of individualised treatment options. Using a couple of the aforementioned markers together seems to be most useful for early diagnosis of tumour disease as well as for assessing treatment response, the presence of tumour progression or further prognosis (Kaszak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular aspects of tumours (metabolism, gene expression, miRNAs and transcriptome sequencing markers) are crucial for a proper understanding of tumour genesis and the application of individualised treatment options. Using a couple of the aforementioned markers together seems to be most useful for early diagnosis of tumour disease as well as for assessing treatment response, the presence of tumour progression or further prognosis (Kaszak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…mammary gland tumours, MGT) zaliczane są do najczęściej diagnozowanych guzów u suk. Szacuje się, że stanowią ponad połowę wszystkich odnotowanych przypadków, a wśród nich 50-70% wykazuje charakter złośliwy [Kaszak i in. 2022].…”
Section: Analiza Czynników Predysponujących Do Rozwoju Nowotworów Gru...unclassified
“…In recent years, there has been a focus on promoting comparative studies on the prognosis and treatment of breast cancer. Numerous authors have confirmed canine mammary tumours (CMTs) as a good spontaneous model for the study of HBC, as they share many similar histological, genetic, morphological, molecular, clinical, and environmental aspects [ 3 ]. CMTs represent the majority of tumours in female dogs, with an incidence of 50–70% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%